Application of geophysical monitoring within the Otway Project S.E. Australia - Urosevic, Milovan; Kepic, Anton; Sherlock, Donald; Daley, T.; Freifeld, B.; Sharma, S.; Dodds, K. (2018)
Copyright © (2008) by the Society of Exploration Geophysicists All rights reserved. The Australian Cooperative Research Centre for Greenhouse Gas Technologies (CO2CRC) is currently injecting 100,000 tons of CO2 in a large scale test of storage technology in a pilot project in South Eastern Australia called the CO2CRC Otway Basin Project (Otway). The Otway Basin with its natural CO2 accumulations and many depleted gas fields, offers an appropriate site for such a pilot project. An 80% CO2 stream is produced from a well (Buttress) near to the depleted gas reservoir (Naylor) used for storage. The goal of this pilot project is to demonstrate that CO2 can be safely transported, stored underground and its behavior tracked and monitored. The monitoring and verification framework has been developed to monitor for the presence and behavior of CO2 in the sub-surface reservoir, near surface and atmosphere. This monitoring framework has been selected to address the areas identified by a rigorous process of risk assessment and subsequently verify conformance to clearly identifiable performance criteria. These criteria have been agreed with the regulatory authorities to manage the project through all phases addressing responsibilities, liabilities and to provide assurance of safe storage to the satisfaction of the public at large.